Pengaruh Pasang Surut Terhadap Profil Muka Air Banjir Bantaran Sungai Musi Kota Palembang - Reni Andayani; Ayu Marlina (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
Palembang is famous for the Musi River with a length of 460 km. The area along the river border is vulnerable to the impact of floods, this is the same thing that occurs in the Gandus District, which is mostly located on the banks of the Musi River. Analysis of the flood water level profile along the banks of the Musi River, which is affected by the tides is needed to find out how big the impact of flooding in the study area is. It aims to determine the type of tide, the amount of flow discharge, and simulation of river water level. Primary data was taken using a current meter to determine the speed of river flow. Some of the secondary data needed are river channel topographic data, rainfall data for 10 years, channel cross-section data and Musi River level data. The analysis was carried out in the form of a simulation of flood water level with the help of the HEC-RAS 5.0.7 program. The tidal type of the Musi River is based on the results of the study in the form of Diurnal Tide, with a watershed area of 2.2 km2 in Gandus District, the runoff discharge is 280.34 m3/s. The simulation results with the help of the HEC-RAS program obtained an average runoff height on the Musi River border of 2.7 m. The high runoff from the simulation can have a negative impact on the surrounding community, so there needs to be serious handling for flood control.